A case analysis of turbulence characteristics and ozone perturbations over eastern China - Qin, Zilin; He, Yang; Zhao, Xiaoran; Feng, Yutao; Yi, Xin (Frontiers in Environmental Science, 2022)
Our knowledge of the vertical variabilities in turbulence and ozone perturbation in the free atmosphere is severely limited because of the scarcity of high-resolution observation data. Based on the Thorpe method, a new set of sounding data in Shanghai, China, was used herein to analyze the distributions of turbulence and ozone perturbation. The region in which turbulence activity is relatively frequent spans from 5-15 km in the middle and upper troposphere. Due to the combined action of large wind shear and thermal convection, the low-troposphere stratification conditions are conducive to the generation of large-scale turbulence. Turbulence has a certain effect on atmospheric ozone concentration exchanges; in most regions located near turbulence, ozone partial pressure perturbations occur. In the troposphere, the ozone profile is most influenced by atmospheric static instability, while in the stratosphere, both wind shear and thermal convection play important roles in the emergence of ozone perturbations.